The role of individual and parental expectations in student-athletes' career adaptability profiles. (March 2022) - Nikander, Jaakko; Tolvanen, Asko; Aunola, Kaisa; Ryba, Tatiana V.
Abstract: Objectives: To support holistic development, adolescent student-athletes are encouraged to integrate sport with education/academics (i.e., dual careers). Career adaptability, as a psychological resource, may help youth athletes cope with transitions and successfully manage their careers. Individuals with a plan and higher expectations for the future demonstrate higher career adaptability and are better prepared for the future. In the present study, we examined what kinds of distinct career adaptability profiles could be identified among youth athletes in Finland at the transition stage to a sports high school (i.e., specialized school for athletes). Moreover, we investigated whether youth athletes' success expectations about school and sport, and corresponding parental expectations, predicted the probability of student-athletes demonstrating a certain career adaptability profile. Next, we examined how gender was represented in the different profiles. Design and methods : The present study is part of the Longitudinal Finnish Dual Career study. A total of 391 student-athletes (51% females) from six sports high schools in Finland, and 448 parents (42% fathers) participated in the study. The student-athletes answered questionnaires on career adaptability (Career Adapt-Abilities Scale – Dual Career Form) and success expectations at the beginning and then again at the end of the first year of sports high school. At the beginning of sports high school, parents responded to a questionnaire about their expectations of success for their children in both academics and in sport. The data were analyzed using structural equation modeling and latent profile analysis. Results: Five distinct adaptability profiles across time were identified: stable, very low adaptability, stable low adaptability, stable moderate adaptability, stable high adaptability, and increased adaptability. Student-athletes' high success expectations in academics and sport, and mothers' high success expectations in academics, increased the probability of student-athletes showing higher adaptability profiles. Conclusions: The student-athletes' high level of expectations for both sport and academics are associated with career adaptability, and mothers' high expectations of student-athletes' academic success relate to higher career adaptability profiles among student-athletes and can thus be considered an important factor in supporting their dual careers. Highlights: Five distinct career adaptability profiles were identified in student-athletes across first year of sports high school. The profiles of career adaptability differed mainly in the general level of adaptabilities rather than in the pattern of change across the school year. Individuals' success expectations in sport and school, and mothers' success expectations in school, predicted the profiles.